The hidden treasure of Glaston - Jewett, Eleanore Myers; Chapman, Frederick T. (Frederick Trench), 1887-1983. (Bathgate, N.D. : Bethlehem Books, 2000)
In 1171 twelve-year-old Hugh, burdened with a crippled leg since birth, is unhappy when his nobleman father, forced into exile in the bloody aftermath of King Henry's confrontation with Archbishop Thomas Becket, leaves him in the care of the monks of Glastonbury Abbey.
Accelerated Reader AR
Newbery Medal Honor Book, 1947.
Keywords: Glastonbury Abbey -- Fiction; Friendship -- Juvenile fiction; People with disabilities -- Juvenile fiction; Monasteries -- Juvenile fiction; Middle Ages -- Juvenile fiction; Great Britain -- History -- Henry II, 1154-1189 -- Juvenile fiction; Adventure stories